Kompetisi Diplomasi: Taiwan (ROC) versus Tiongkok (PRC) di Kepulauan Solomon tahun 2016-2019 - Victoria Amandani Santoso; Reni Windiani; Satwika Paramasatya (Jurnal Hubungan Internasional, 2021)
The relationship between China and Taiwan is on enduring rivalry for the lastfive decades regarding their identity, territory, and national sovereignty. FromChina’s perspective, Taiwan is an inseparable part of Mainland China, thereforeevery forms of self independence are not accepted. Meanwhile from Taiwan’sperspective, it is a sovereign state that doesn’t abide to “One China, Two System”principle. The competition of those two often involves diplomacy to obtain formalrecognition from other countries to maintain its legitimacy and rights as astate. On September 2019, Solomon Island, which had been in relationship for36 years with Taiwan, decided to change its formal recognition and supportedChina. The author uses Joseph Nye Jr’s Soft Power Theory with library researchdata collection methods and congruent data analysis methods. This paper aimsto analyze the form of Taiwan and China policies through the concept of softpower and understanding the influence of those two countries’ policies to thedecision of the Solomon Island. The results proves that China’s soft power is superiorto Taiwan’s soft power from the perspective of Solomon Islands.